Мотив самотності в поезії Тодося Осьмачки: екзистенціально-діалогічна інтерпретація - Токмань, Г. (Слово і Час, 2020)
Стаття присвячена поезії Тодося Осьмачки, увага сфокусована на мотиві самотності у віршах зі збірки «Китиці часу». Дослідниця аналізує художній текст та інтерпретує його екзистенціальні смисли. Самотність людини в поезії Т. Осьмачки викликана історичними подіями, еміграцією, відсутністю друга й коханої. Філософські висловлювання поета окреслюють сутність самотності людини в її унікальному індивідуальному існуванні. Наведено положення із праць філософів М. Гайдеґґера, Х. Ортеги-і-Гассета, Г. Марселя, які допомагають витлумачити художній текст Т. Осьмачки. Діалог між поезією й екзистенціальною філософією розкриває значення художніх образів і виявляє специфіку мистецтва. Визначено риси індивідуального стилю Т. Осьмачки як автора філософської лірики. The paper deals with the works by the Ukrainian poet Todos Osmachka (1895—1962). Attention is focused on the motive of loneliness in the poems from the collection “The Tassels of Time” (1953). Taking into account the memories of the poet’s contemporaries, the researcher analyzes the texts and interprets their existential meanings. The poems contain both individual facts of human life and philosophical generalizations. The loneliness of T. Osmachka’s lyrical character is caused by historical events, emigration, the absence of friends and his beloved one. The hero is an artist, so he needs a reader who can understand and feel his work. The poet expresses feelings of an emigrant writer who left his unhappy occupied country. The poems depict the author’s life among people who are strangers for him in terms of spirit. The poet needs loneliness for his creative work, and it is high loneliness of spirit. Osmachka’s philosophical statements make sense of the human solitude as a feature of unique individual existence. The researcher cites the works of philosophers M. Heidegger, J. Ortega y Gasset, G. Marcel, which help to interpret T. Osmachka’s texts. M. Heidegger’s ideas of being-toward-death, Dasein, human self, essential loneliness, and others were used as parallels to the poetic texts. The researcher refers to the theses of Ortega y Gasset’s philosophy concerning loneliness as the initial state of a man and attempts to find the Other, friendship, and love. The article also uses the theory by Marcel on the phenomenology and metaphysics of hope. The dialogue between poetry and existential philosophy reveals the meanings of poetic images and specifics of creative work. The analysis allowed the researcher to define some distinctive style features of T. Osmachka’s philosophical poems and indicate some samples of expressionistic and surrealistic poetics in his works.